W-Shaped Bright Soliton of the (2+1)-Dimension Nonlinear Electrical Transmission Line - İnç, Mustafa; Alqahtani, Rubayyi T. T.; Agarwal, Ravi P. P. (Mdpi, 2023)
In this paper, we investigate solitary wave solutions of the nonlinear electrical transmission line by using the Jacobi elliptic function and the auxiliary equation methods. We obtain Jacobi elliptic function solutions as well as kink, bright, dark, and W-shaped solitons as a result. For specific values of the Jacobi elliptic modulus, we depict bright, dark, and W-shaped soliton solutions as suitable parameters of the structure. Using the auxiliary equation method gives the combined bright-bright and dark-dark optical solitons in optical fibers. One result emerges from this analysis: the potential parameters and free parameters of the method can be employed to degenerate W-shaped bright and dark solitons. The acquired results are general and can be used for many applications in nonlinear dynamic systems.
Keywords: Jacobi elliptic function; nonlinear electrical transmission line; W-shaped profile